Development of a method for measuring low energy electron beam irradiation parameters by calorimetry and step stacking - LUO Rui; ZHANG Yuhe; MAO Naqing (Fushe yanjiu yu fushe gongyi xuebao)
Electron beam irradiation processing has become an important component of the nuclear technology industry, with low-energy electron beam increasingly being applied in processes such as coating curing, wastewater treatment, and food preservation. Accurate measurement of irradiation parameters is essential to ensure irradiation quality. However, at present, standardized protocols for electron beam dosimetry below 300 keV have not been established. As a result, parameter measurements are often benchmarked against the 10 MeV electron linear accelerator, which introduces systematic biases due to inconsistencies among measured objects. In this study, a novel method for measuring low-energy electron beam energy, combining experimental testing and mathematical simulations, was applied to electron beams with energies below 300 keV. Additionally, an absorbed dose measurement device based on calorimetry was developed. Relationships between absorbed dose and beam intensity, displacement velocity, and other parameters were explored to obtain absolute measurements of absorbed doses from a low-energy electron beam. The energy parameters of low-energy electrons were experimentally determined using a dose step-stacking method, combined with simulations of energy deposition depth distribution curve, then the low-energy electron absorbed dose parameters were measured in the range of 140 keV. The low-energy electron absorbed dose parameters were measured using calorimetry in the range 1‒120 kGy, and measurement uncertainty was 11% (k‍=2). This study provides a reliable measurement method for low-energy electron-beam irradiation processing.